EKSPERIMENTASI PEMBELAJARAN MATEMATIKA DENGAN MODEL PEMBELAJARAN KOOPERATIF MELALUI MMP (MISSOURI MATHEMATICS PROJECT) DAN GI (GROUP INVESTIGATION) DITINJAU DARI KECERDASAN EMOSIONAL DAN GAYA BELAJAR SISWA PADA SISWA SMP DI KOTA BLITAR - Suwito, Abi (Department of Mathematics Education , University of Jember, 2013)
Abstract.This research is a quasi experimental research with factorial design of 3x3x3. The population is all grade VIII students of Junior high School in Blitar. The samples are taken using stratified cluster random technic. The samples are 106 students for experimental class I, 104 students for experimental class II, and 107 students for experimental class III of total 317 students. The instruments used for collecting data are the result of semester II final test, emotional intelligence questionnaire, learning style questionnaire, and mathematics learning achievement tests. The testing of questionnaire instrument includes content validity, internal consistency, and realibility. The testing of mathematics tests includes content validity, difficulty level, discrimination power, and realibility. The testing of normality uses Liliefors test, The testing of homogenity uses Bartlett test. The balance test used is one way anava with different cell to know the same initial mathematics ability. The testing of mathematic tests uses three ways – variant analysis with different cell. Key Words: Mechanistic, MMP, GI, Emotional Intelligence, Learning Style